2023
DOI: 10.1192/bjp.2023.21
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and behavioural interventions for the negative symptoms of schizophrenia: a systematic review of efficacy meta-analyses

Abstract: Background Currently there is no first-line treatment recommended for the negative symptoms of schizophrenia. Psychosocial and behavioural interventions are widely used to reduce the burden of negative symptoms. Meta-analytic studies have summarised the evidence for specific approaches but not compared evidence quality and benefit. Aim To review and evaluate the evidence from meta-analytic studies of psychosocial and behavioural interventions for the negative symptoms of schizophrenia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…The EPA relied on evidence from a high-quality meta-analysis involving 2500 participants from different countries and settings that demonstrated that cognitive remediation has a positive effect on negative symptoms. 4 That meta-analysis and the one by the same group, included in this issue (Cella et al 5 ), demonstrated that the cognitive remediation effect on negative symptoms was the same as available pharmacological and behavioural interventions designed to tackle negative symptoms directly.…”
Section: Treating Negative Symptomsmentioning
confidence: 90%
See 1 more Smart Citation
“…The EPA relied on evidence from a high-quality meta-analysis involving 2500 participants from different countries and settings that demonstrated that cognitive remediation has a positive effect on negative symptoms. 4 That meta-analysis and the one by the same group, included in this issue (Cella et al 5 ), demonstrated that the cognitive remediation effect on negative symptoms was the same as available pharmacological and behavioural interventions designed to tackle negative symptoms directly.…”
Section: Treating Negative Symptomsmentioning
confidence: 90%
“…Although treating primary negative symptoms is still an open question, cognitive remediation should be considered as a first-line treatment for improving cognition and functioning. For the future we already know that different psychological treatments show significant effects on negative symptoms, but the review by Cella et al 5 stressed that the methodology of the cognitive remediation studies suggests that cognitive remediation effects are more robust compared with the other approaches. The current available evidence therefore positions cognitive remediation as a strong candidate for reducing the severity of negative symptoms whether primary or secondary.…”
Section: Is It Time Yet?mentioning
confidence: 99%
“…The reviewed literature lacks both clear inclusion criteria and adequate information pertaining to adherence to the FITT-VP parameters, which are essential for the purposes of prescribing exercise and facilitating the replicability of research findings [28,29]. These deficiencies persist in recent reviews published within the last year [36][37][38][39][40]. Thus, for this new review it is imperative to incorporate elements addressing these issues into the selection criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Psychotherapeutic and social integration practices have increasingly been included in therapeutic guidelines in addition to the pharmacological treatment, to improve quality of life. A recent systematic review of efficacy meta-analyses on psychosocial and behavioral interventions in schizophrenia (2) highlights the most cited ones in the literature: CBT and cognitive based interventions, social skills training, acceptance, and mindfulness based approaches, family interventions, exercise therapy, music therapy, as well as befriending, although no evidence was found in support of befriending as being superior to other interventions. Within this approach, befriending stands as an intervention of interest, still, as it is one of the most easily available approach.…”
Section: Introductionmentioning
confidence: 99%